On the strict convexity of the Besicovitch-Orlicz space of almost periodic functions with Orlicz nor - Morsli, Mohamed; Bedouhene, Fazia (Revista Matemática Complutense, 2003)
The problem of strict convexity of the Besicovitch-Orlicz space of almost periodic functions is considered here in connection with the Orlicz norm. We give necessary and sufficient conditions in terms of the function Á generating the space.